Web 2.0 and the Semantic Web: new horizons for education - Špiranec, Sonja; Banek Zorica, Mihaela (2008)
It was long believed that the open and distributed nature of the Web as we know it provides the setting for the implementation of new educational paradigms. Nevertheless, very soon it became clear that the existing Web, or Web 1.0, is not an ideal environment for the essential reconfiguration of learning practices. But as the concepts of Web 2.0 and the Semantic web have entered the information domain, new horizons for education came into sight. The concept of Web 2.0 has changed much of how one approaches to and uses the web, while it is believed that the Semantic web will eliminate many shortcomings that determine their Web experience today. Both concepts provide capacities of restructuring information landscapes. Since new pedagogical paradigms are based on the premise of constant interactions with complex information environments, the Web 2.0 and the Semantic web could significantly enhance educational processes. In the paper, the authors will give an overview of the notion of Web 2.0 which services are already a vital element of educational endeavours, and the Semantic web, which currently exists mere in the form of visions, but with very clear projections of the benefits it could bring to education. After analysing both concepts, the authors will present concrete scenarios of Education 2.0 and the Educational semantic web.
Projekt MZOS
ENG